2007
DOI: 10.1007/s00415-006-0488-1
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic correlates of executive dysfunction

Abstract: This study was designed to examine the correlations between resting-state brain glucose metabolism (CMRglc), as measured with Positron Emission Tomography and performance on executive function tasks in Alzheimer's disease (AD), while taking into account the severity of cognitive deterioration. We addressed this issue in 50 AD patients, classified as very mild (n = 22) and mild (n = 28) AD on the basis of an extensive neuropsychological battery. Thirteen healthy subjects were selected as controls for the neurop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 115 publications
1
12
0
1
Order By: Relevance
“…So far, few imaging studies have related deficits in classical executive tests such as the Stroop interference or fluency task to atrophy and hypometabolism in prefrontal regions in FTLD, Alzheimer's disease and mild cognitive impairment (Salmon et al ., 2006, 2008, 2009; Teipel et al ., 2006; Bracco et al ., 2007; Grossman et al ., 2007; Huey et al ., 2009; Pa et al ., 2009; Raczka et al ., 2010), although it is well known that these regions are altered in these diseases (Thompson et al ., 2003; Apostolova et al ., 2007; Schroeter et al ., 2007 c , 2008, 2009; Barthel et al ., 2011). …”
Section: Introductionmentioning
confidence: 99%
“…So far, few imaging studies have related deficits in classical executive tests such as the Stroop interference or fluency task to atrophy and hypometabolism in prefrontal regions in FTLD, Alzheimer's disease and mild cognitive impairment (Salmon et al ., 2006, 2008, 2009; Teipel et al ., 2006; Bracco et al ., 2007; Grossman et al ., 2007; Huey et al ., 2009; Pa et al ., 2009; Raczka et al ., 2010), although it is well known that these regions are altered in these diseases (Thompson et al ., 2003; Apostolova et al ., 2007; Schroeter et al ., 2007 c , 2008, 2009; Barthel et al ., 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Prior work has suggested the Stroop interrogates a bilateral network, and that the right insula in particular may be important for task monitoring across a number of different types of inhibition tasks (Cieslik, Mueller, Eickhoff, Langner, & Eickhoff, 2015). Prior work on Color-Word condition in dementia has found support for left laterialized frontal involvement in very mild AD (Bracco et al, 2007) or a mixed sample of dementia patients (Schroeter et al, 2012), right lateralized involvement in mild AD (Bracco et al, 2007), or bilateral frontal involvement in AD (Yun et al, 2011) and a mixed sample of dementia (Heflin, 2011). The heterogeneity is likely driven by differences in methodology, the patients being studied, and the severity of cognitive impairment in the cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies (Bracco et al, 2007; Yun, 2011) have utilized several measures of interference, some of which do not account for such slowing. Lansbergen, Kenemans, & van Engeland (2007) describe the problematic nature of two common methods of measuring interference: 1) difference scores between individual Color and Word scores and Color-Word, and 2) differences between a predicted Color-Word score and actual Color-Word score (Golden, 1978; Lansbergen, Kenemans, & van Engeland, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is already known that the source of FRN is located in the ACC (Holroyd and Coles, 2002; Hajcak et al, 2007; Bellebaum and Daum, 2008; Holroyd et al, 2009), and abnormalities of the ACC in AD have been reported at histopathological and physiological levels. In AD patients, accumulation of both beta amyloid and tau (Morishima-Kawashima and Ihara, 2002; Leuba et al, 2009; Murphy and LeVine, 2010; Bloom, 2014), metabolic changes (Bracco et al, 2007; Lim et al, 2012), and decreased blood flows (Dukart et al, 2013; Long et al, 2013; Terada et al, 2013; Lin et al, 2014; Bailly et al, 2015) are observed in the ACC. The ACC is atrophied structurally (Buckner et al, 2005; Jones et al, 2006; Seeley et al, 2009; Krueger et al, 2010), and the anatomical connectivity with other areas is also impaired (Greicius et al, 2004; Rombouts et al, 2005; Wang et al, 2007; Boublay et al, 2016; Hafkemeijer et al, 2016b).…”
Section: Discussionmentioning
confidence: 99%